The Role of Physical Therapy in Multiple Risk Factor Management Poststroke: A Scoping Review. Issue 3 (5th July 2021) - Sutton, Kathleen M.; Hunter, Elizabeth G.; Logsdon, Brooke; Santella, Brittney; Kitzman, Patrick H.
Abstract : Background and Purpose: Individuals after stroke often have multiple chronic conditions, such as hypertension, diabetes, dyslipidemia, obesity, and tobacco use. These comorbidities not only are commonly found in individuals with stroke, but also negatively affect functional outcomes and increase risk for hospital readmission and overall mortality. It is important for physical therapists to address the whole person during treatment after stroke, including comorbidities, not just the problems resulting from the stroke itself. However, it is unclear how common it is for physical therapists to address multiple diagnoses at once using a wellness model. Therefore, the purpose of this scoping review was to examine current evidence regarding the role of physical therapy in addressing modifiable risk factors for individuals after stroke, to identify gaps in research associated with physical therapy management of related comorbid diagnoses during treatment for stroke. Methods: A scoping review methodology was utilized searching PubMed and CINAHL databases to identify interventional research studies specifically addressing multiple modifiable risk factors utilizing physical therapy for individuals after stroke. Results: The initial search yielded 5358 articles and 12 articles met full inclusion criteria. Only 2 studies included participants with significant mobility impairments, and none included individuals with communication impairments. Only 4 of the 12 studies provided education in their design. Eight studies did not include any patient-reported outcome measures. Only 3 studies included long-term follow-up assessments. Discussion: Secondary stroke risk factors can be positively addressed using physical therapy interventions; however, more research is needed regarding individuals with moderate to severe mobility or communication deficits. Opportunities for physical therapy research to address stroke risk factors in this complex population include expanding follow-up periods, improving educational interventions, and including caregivers in study design. Conclusions: This review highlights the need for better integration of clinical considerations into stroke rehabilitation research as a whole, along with the need for additional research regarding the role physical therapy can play in addressing multimorbidity in individuals with stroke.